Assessment of the Sensitivity of Some Plant Pathogenic Fungi to 6-Demethylmevinolin, a Putative Natural Sensitizer Able to Help Overcoming the Fungicide Resistance of Plant Pathogens - Larisa Shcherbakova; Maksim Kartashov; Natalia Statsyuk; Tatyana Pasechnik; Vitaly Dzhavakhiya (MDPI AG, 2020)
Agricultural fungicides contaminate the environment and promote the spread of fungicide-resistant strains of pathogenic fungi. The enhancement of pathogen sensitivity to these pesticides using chemosensitizers allows the reducing of fungicide dosages without a decrease in their efficiency. Using Petri plate and microplate bioassays, 6-demethylmevinolin (6-DMM), a putative sensitizer of a microbial origin, was shown to affect both colony growth and conidial germination of Alternaria solani, A. alternata, Parastagonospora nodorum, Rhizoctonia solani, and four Fusarium species (F. avenaceum, F. culmorum, F. oxysporum, F. graminearum) forming a wheat root rot complex together with B. sorokiniana. Non- or marginally toxic 6-DMM concentrations suitable for sensitizing effect were determined by the probit analysis. The range of determined concentrations confirmed a possibility of using 6-DMM as a putative sensitizer for the whole complex of root rot agents, other cereal pathogens (A. alternata, P.nodorum), and some potato (R. solani, A. solani) and tomato (A. solani) pathogens. Despite the different sensitivities of the eight tested pathogens, 6-DMM lacked specificity to fungi and possessed a mild antimycotic activity that is typical of other known pathogen-sensitizing agents. The pilot evaluation of the 6-DMM sensitizing first confirmed a principal possibility of using it for the sensitization of B. sorokiniana and R. solani to triazole- and strobilurin-based fungicides, respectively.